Financial discrepancies in political party funding by Indonesian local government authorities - Taplin, Ross; Rusmin, Rusmin; Brown, Alistair (Taylor and Francis, 2013)
Through different forms of decentralization variables, this study investigates Indonesian local government authorities' 2006 financial accountability reports in terms of local government authorities' contributing funds to political parties. Audit results by the Supreme Audit Body reveal that many articles were violated by these authorities in regard to the distributing, administrating, and reporting of assistance funds from them to political parties. Each rupiah committed by the 221 local government authorities involved in this study violated, on average, 1.8 articles, indicating a low level of compliance. Critically, the study finds that administrative, fiscal, and political decentralization decreases discrepancies. The less administratively decentralized provincial authorities, where decision making is a level of government farther from the people, are more likely than non-provincial local government authorities to make discrepancies with political party legislation and regulations. Fiscally decentralized local government authorities, who earn a higher fraction of their revenue from local sources, also tend to have fewer discrepancies. Finally, politically decentralized authorities with a higher percentage of elected officials from the decentralized supporting ruling coalition, also have fewer discrepancies.